Centralized Reserves Pooling for the Asean-5 to China and India - Ahmad Sazali, Zakaria (2011)
With the emergence of China and India, the international reserves pooling scheme landscape of ASEAN and its relation to the global economy have changed. This study adopts the Pedroni Panel Cointegration test to examine the long run relationship between the determinants of reserves pooling in Indonesia, Malaysia, the Philippines, Singapore and Thailand (ASEAN-5) and the determinants of reserves pooling in China and India. The determinants of reserves pooling in this study are the total population of the country, real GDP per capita, the volatility of real export receipts, the share of imports in GDP, the volatility of nominal effective exchange rate and fixed capital formation to show reserves pooling behavior. Generally speaking, the results indicate that all of the determinants of reserves pooling in ASEAN-5 have different long run relationship when they are pooled to China and India. It is important to understand the determinants of reserves pooling because each determinant has a different relationship in different models of countries that they are pooled.